Guerothrips moundi, gen. et sp.n. (Thysanoptera, Thripidae) from Chiapas, Mexico - Goldarazena, Arturo; Infante, Francisco (Zootaxa, 2013)
Guerothrips moundi gen. et sp. n., (Thripidae, Thripinae) is described from flowers of the herbaceus plant Waltheria in-dica (Sterculiaceae) found in Tapachula, Chiapas, Mexico. G. moundi is a member of the Frankliniella genus-group, but is distinguished by the presence of sternal discal setae on the abdomen. The available specimens are all brachypterous.